Coal not becoming superfluous - Fritz Hellwig (Intereconomics, 1967)
The rapid change in the European energy sector has mainly affected the coal. It is more and more threatened to lose its importance. The importance of exploitation and transport means increasing competitivenes of non-European suppliers, and technical progress enables the economical use of new power categories. For the adjustment of coal demand to the present and future one, many-sided politico-economical measures and programmes are imperative. INTERECONOMICS had the occasion to talk with Dr Hellwig, Vice President of the Commission of the European Communities, about these questions.
Keywords: 330; Interview